Noninvasive Combined Diagnosis and Monitoring of Aspergillus and Pseudomonas Infections: Proof of Concept - Dobiáš, Radim; Škríba, Anton; Pluháček, Tomáš; Petřík, Miloš; Palyzová, Andrea; Káňová, Marcela; Čubová, Eva; Houšť, Jiří; Novák, Jiří; Stevens, David A; Mitulovič, Goran; Krejčí, Eva; et al. (Journal of fungi (Basel, Switzerland), 2021)
In acutely ill patients, particularly in intensive care units or in mixed infections, time to a microbe-specific diagnosis is critical to a successful outcome of therapy. We report the application of evolving technologies involving mass spectrometry to diagnose and monitor a patient's course. As proof of this concept, we studied five patients and used two rat models of mono-infection and coinfection. We report the noninvasive combined monitoring of Aspergillus fumigatus and Pseudomonas aeruginosa infection. The invasive coinfection was detected by monitoring the fungal triacetylfusarinine C and ferricrocin siderophore levels and the bacterial metabolites pyoverdin E, pyochelin, and 2-heptyl-4-quinolone, studied in the urine, endotracheal aspirate, or breath condensate. The coinfection was monitored by mass spectrometry followed by isotopic data filtering. In the rat infection model, detection indicated 100-fold more siderophores in urine compared to sera, indicating the diagnostic potential of urine sampling. The tools utilized in our studies can now be examined in large clinical series, where we could expect the accuracy and speed of diagnosis to be competitive with conventional methods and provide advantages in unraveling the complexities of mixed infections.
Keywords: noninvasive diagnosis; Aspergillus fumigatus; virulence factor; quorum-sensing molecules; invasive infection; Pseudomonas aeruginosa; siderophores; coinfection